KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMP PADA MATERI TEOREMA PHYTAGORAS BERBASIS SOAL HOTS (HIGT ORDER THINGKING SKILL) DITINJAU DARI PEMAHAMAN KONSEP - Tukino Tukino; Nurhanurawati Nurhanurawati; Sri Hastuti Noer (Universitas Muhammadiyah Metro, 2023)
Problem solving is one of the Higher Order Thinking Skills (HOTS). Educational demands in the 21st century all learning is directed at learning high-level thinking and being able to solve problems, bearing in mind that Indonesia's 2018 PISA results are still below average and starting in 2021 the National Examination will be abolished and replaced with AKM whose questions are of the HOTS type. As well as the results of the 2021 National Assessment at the Cendikia Tulang Bawang Integrated Islamic Middle School showing the results of students' mathematical literacy reaching a minimum competency with a distribution of student abilities of 4.65% proficient, 51.16% proficient, 41.86% fundamental and 2.3% needing intervention . The purpose of this study was to determine the mathematical problem solving skills of junior high school students on the Pythagorean theorem material based on higher order thinking skills (HOTS) questions in terms of conceptual understanding. This study used a qualitative descriptive method with high, medium, and low concept understanding student categories. The results of this study on average have been able to understand the existing problems, but in the implementation stage of problem solving only medium and high students were able to solve them correctly.